The Role of Risk Management in Mediating Corporate Governance on Financial Performance in Banking Companies in Indonesia - Hermawan, Hermawan; Hersugondo, Hersugondo (Dinasti Publisher, 2026)
Improving shareholder welfare requires strong financial performance, as it enhances a company's market value and facilitates access to external capital through loans or equity investments. Solid financial performance builds investor confidence and encourages expectations of higher returns. The decline of the banking sector during past crises was not solely due to weak implementation of good corporate governance (GCG), but also inadequate risk management, highlighting the growing importance of integrating effective risk controls with GCG principles to strengthen firm value. This study empirically analyzes banking companies listed on the Indonesia Stock Exchange during 2020–2023 using secondary data from publicly available financial and annual reports on [www.idx.co.id](http://www.idx.co.id). Employing a quantitative descriptive design with partial regression analysis, the study examines statistical patterns and variable relationships. The findings reflect that high investment levels often correspond with lending practices that carry significant credit risk, requiring larger loan-loss reserves. Financial institutions can mitigate such risks by limiting high-risk activities and transferring manageable risks to other entities. Overall, financial performance represents the company’s ability to manage resources effectively and comply with financial governance standards, ultimately shaping stakeholder trust and corporate sustainability.